Investigation of the Ultrasonic Stimulation Performance on Permeability Enhancement in Coal Seam: Field Tests and In Situ Permeability Evaluation - Jinbiao Fei; Peng Liu; LongKang Wang; Fangxiang Zhong; Chenglong Xie; Yongdong Jiang; Quangui Li; Mingyang Liu (Geofluids)
Power ultrasonic-assisted reservoir modification is a promising technique for enhanced coalbed methane recovery. However, the in-site performance of ultrasound-assisted CBM production has not yet been revealed. In the current study, the in situ antireflection test was conducted with high-power ultrasound ~18 kW in underground coal seam, and the antireflection performance was investigated by measuring the borehole drainage gas data in the field test zone, and then, the in situ permeability change of the target coal seam was evaluated numerically. The result shows that, within 40 days’ drainage after ultrasonic antireflection in coal seam, the average gas concentration of single borehole in the experimental group increased by 81.4 %~227.3% than that in control group, the average borehole gas flowrate has a 20%~106% improvement over the control group, and the pure methane production in single borehole increased by about 3.83 times. The permeability inversion indicates that the in situ coal seam permeability has increased by at least 2.36 times after the ultrasound stimulation within the range of 8 m from the ultrasound source.